Inventário e orientação para sequenciamento de prevalência em apreciação de riscos em dobradeira HD-CNC - Kelm, Marcelo Fernando (Universidade do Vale do Rio dos Sinos, 2015)
The NR-12 establishes principles of security, prevention and measures of occupational hygiene to be adopted in machinery and equipment, aimed at the prevention of industrial accidents. Thus, the objective of this work is to guide and educate businesses and professionals to the prevention culture is at the heart of their management plans in the area of occupational health and safety. The use of concepts to identify hazards and measure the risks in assists in strategies to prioritize inspections of the conditions of the machinery or equipment, carrying out of your inventory and risk assessment, indicating the situation that they find themselves. The application of the standard NR-12, in addition to a legal requirement, guarantee the physical integrity of workers, guides the compliance in the direct relationship between man and machine, suitability and continuous improvement
Keywords: Inventário; Apreciação de risco; HRN; Inventory; Assessment of risk